Graph Models for Identifying Robot-Packable Patterns of Pallet Loading - Krzysztof Pieńkosz (Operations Research and Decisions, 2024)
In the logistics processes of trade business, goods delivered from warehouses to retailers are often transported on pallets. The paper concerns the issue of using a robot for automatic palletizing. In order to put an item in a given place on a partially loaded pallet, the robot must have free access to that place, i.e., the place must not be covered. A graph model and a formalized method for determining the sequence of putting goods on a pallet is proposed to avoid such collisions. It is also shown that not every packing pattern can be loaded by a robot. However, some pallet loading approaches have been identified that always guarantee a feasible robot packing. (original abstract)